Olive shootworm, Palpita persimilis Munroe (Insecta: Lepidoptera: Crambidae) - James E. Hayden; Lyle J. Buss (EDIS)
Palpita persimilis Munroe (Lepidoptera: Crambidae) is a defoliator of olives and privet in South America. Examination of specimens submitted to UF-IFAS and FDACS-DPI prompted the discovery that the species has been established in Florida for many years, having been confused with two similar native species. The confusion parallels historical misidentifications in Peru. To date, all vouchered specimens in Florida with host information were found feeding on leaves of Ligustrum japonicum Thunb. (Japanese privet). This 6-page fact sheet was written by James E. Hayden and Lyle J. Buss and published by the UF Department of Entomology and Nematology, May 2013.